Respuesta :

[tex]\huge\text{Hey there!}[/tex]

[tex]\huge\textbf{Equation:}[/tex]

[tex]\mathbf{6x + 2 = 2x - 1}[/tex]

[tex]\huge\textbf{SUBTRACT 2x to BOTH SIDES:}[/tex]

[tex]\mathbf{6x + 2 - 2x = 2x - 1 - 2x}[/tex]

[tex]\huge\textbf{Simplify it!}[/tex]

[tex]\mathbf{4x + 2 = -1}[/tex]

[tex]\huge\textbf{SUBTRACT 2 to BOTH SIDES:}[/tex]

[tex]\mathbf{4x + 2 - 2 = -1 - 2}[/tex]

[tex]\huge\textbf{Simplify it!}[/tex]

[tex]\mathbf{4x = -3}[/tex]

[tex]\huge\textbf{DIVIDE 4 to BOTH SIDES:}[/tex]

[tex]\mathbf{\dfrac{4x}{4} = \dfrac{-3}{4}}[/tex]

[tex]\huge\textbf{Simplify it!}[/tex]

[tex]\mathbf{x = \dfrac{-3}{4}}[/tex]

[tex]\mathbf{x = -\dfrac{3}{4}}[/tex]

[tex]\huge\text{Therefore, your answer should be: \boxed{\mathsf{x = -\dfrac{3}{4}}}}\huge\checkmark[/tex]

[tex]\huge\text{Good luck on your assigiment \& enjoy your day!}[/tex]

~[tex]\frak{Amphitrite1040:)}[/tex]